Phylogeny of Thripophagini ovenbirds (Aves: Synallaxinae: Furnariidae). (1st June 2019) - Quintero, Esther; Perktaş, Utku
Abstract: In this study, we address the evolutionary relationships and discuss the biogeographical history of a complex and diverse group of ovenbirds, the Thripophagini. We reconstruct the phylogeny and estimate the time of divergence of this group, using sequences from two complete mitochondrial genes (cytochrome b and NADH subunit 2) from a total of 115 fresh tissue samples. The results provide a better understanding of the phylogenetic relationships of the taxa within this group, some of which require a thorough taxonomic revision. We discuss the biogeographical history of the group, and find parallels with other previously studied Andean birds which may indicate that tectonic and climatic events might, at least in part, be linked to its diversification through the uplift of the Andes, the creation of new montane habitats and barriers, the evolution of Amazonian drainages and landscapes, and the climatic oscillations of the Pleistocene.